2022
DOI: 10.1111/bph.15836
|View full text |Cite
|
Sign up to set email alerts
|

High glucose‐mediated VPS26a down‐regulation dysregulates neuronal amyloid precursor protein processing and tau phosphorylation

Abstract: Background and Purpose: The relationship between hyperglycaemia-induced retromer dysfunction impairing intracellular trafficking and Alzheimer's disease (AD) remains unclear, although diabetes mellitus (DM) is considered a risk factor for AD. Here, we investigated the effects of high glucose on the retromer and defined the dysregulation of mechanisms of amyloid precursor protein (APP) processing and tau phosphorylation.Experimental Approach: We used human induced-pluripotent stem cell-derived neuronal differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…Likewise, in human iPSC-derived neurons from patients with AD, both R33 and R55 reduced tau phosphorylation in an APP-independent manner (Young et al, 2018). Finally, a recent cellular and animal model study demonstrated that the administration of R33 ameliorated the retention of APP in EE and increased the level of phosphorylated tau under high glucose condition (Chae et al, 2022). Taken together, these results open up a new therapeutic avenue for targeting retromer in AD.…”
Section: Considerations For Retromer As a Therapeutic Target In Alzhe...mentioning
confidence: 87%
“…Likewise, in human iPSC-derived neurons from patients with AD, both R33 and R55 reduced tau phosphorylation in an APP-independent manner (Young et al, 2018). Finally, a recent cellular and animal model study demonstrated that the administration of R33 ameliorated the retention of APP in EE and increased the level of phosphorylated tau under high glucose condition (Chae et al, 2022). Taken together, these results open up a new therapeutic avenue for targeting retromer in AD.…”
Section: Considerations For Retromer As a Therapeutic Target In Alzhe...mentioning
confidence: 87%
“…Dot blot analysis was used to determine the DNA methylation status of the SH-SY5Y cells. Using a genomic DNA extraction kit, genomic DNA (gDNA) was extracted (Bioneer, K-3032) [ 34 ]. The 100 ng of extracted gDNA was denatured for 10 min at 95 °C and then neutralized on ice for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…EZ DNA methylation-lightning kit was used to analyze the methylation of gDNA by bisulfite treatment [ 34 ]. EZ DNA Methylation-Lightning Kit (D5030) was purchased from Kyongshin Scientific company (Seoul, Korea).…”
Section: Methodsmentioning
confidence: 99%
“…Vacuolar protein sorting associated protein 26 A (VPS26A) functions as a subunit of a large polymeric complex, named the retromer complex, which mediates retrograde trafficking from endosomes to the trans-Golgi network of divert proteins [ 6 , 7 , 8 , 9 ]. To date, investigations into the role of VPS26A in physiology and pathology have focused on neuroscience [ 10 , 11 , 12 , 13 , 14 ]. During neurogenesis, VPS26A promotes the transition of stemness to differentiation through crosstalk with the Nox4/ROS/ERK1/2 cascade in embryonic stem cells [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…VPS26A expression was shown to be decreased in individuals with Alzheimer’s disease [ 15 ]. The down-regulation of VPS26A dysregulates amyloid precursor protein processing and tau phosphorylation in neurons [ 13 ]. However, the expression and role of VPS26A in cancer occurrence and development remain largely unclear, except for two recent studies, which revealed that VPS26A is a candidate prognosis gene for hepatocellular carcinoma [ 16 ] and that VPS26A is induced in a senescent bladder cancer cell line EJ by the forced expression of p21 or p16 in vitro [ 17 ].…”
Section: Introductionmentioning
confidence: 99%